2019
DOI: 10.1039/c9ra06966f
|View full text |Cite
|
Sign up to set email alerts
|

Facile liquid-assisted one-step sintering synthesis of superfine L10-FePt nanoparticles

Abstract: A liquid-assisted one-step sintering method was proposed for the synthesis of L10-FePt superfine nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…From the TEM images, it can be found that the shape-anisotropic concave-cube NPs transform to sphere after annealing, the size uniformity is poor and some NPs had grown abnormally in the annealed samples. Although the NaCl medium is employed to avoid aggregation of the NPs during annealing, the random abnormal growth of the NPs is still unavoidable [11,26]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the TEM images, it can be found that the shape-anisotropic concave-cube NPs transform to sphere after annealing, the size uniformity is poor and some NPs had grown abnormally in the annealed samples. Although the NaCl medium is employed to avoid aggregation of the NPs during annealing, the random abnormal growth of the NPs is still unavoidable [11,26]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The shape anisotropy of concave-cube FePt NPs is originated from the over-growth of truncated-cube or cube seeds along < 111 > direction, and the Pt contents is richer at corner-site, which leads to the element distribution anisotropy [5][6][7]. Otherwise, the as-synthesized FePt NPs always shows a disorder fcc structure, the annealing is required to form an orderly L1 0 -phase with better magnetic and electrocatalytic performances [8][9][10][11]. The typical anisotropy of shape and element, and the meaningful disorder-order transition of concave-cube fcc-FePt NPs offer us a good option to study the microstructure and property evolution of anisotropic NPs during annealing.…”
Section: Introductionmentioning
confidence: 99%
“…The L1 0 -FePt@Bi-rich NPs were synthesized by simultaneous thermal decomposition and reduction of Fe, Pt, and Bi precursors. 36 Firstly, 0.25 mmol Pt(acac) 2 (acac = acetylacetonate), 0.25 mmol Fe(acac) 3 and 0.2 mmol Bi(Ac) 3 (Ac = acetate) were dissolved in 10 ml of hexadecylamine solvent in a 100 ml three-neck flask, and then 0.75 mmol 1,2-hexadecanediol was added as a reductant. Subsequently, the mixture was heated to 120 °C under an Ar atmosphere, and electromagnetic stirring was performed for 30 minutes to remove water.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Although the NaCl medium is employed to avoid aggregation of the NPs during annealing, the random abnormal growth of the NPs is still unavoidable. 11,35 As shown in Fig. 1(e 1 )-(e 4 ), the lattice fringes of as-synthesized, 0 T-annealed, and 12 Tannealed FePt NPs display interplanar spacing of 0.195, 0.273, 0.216 and 0.225 nm in the particle, which match well respectively with those of the A1-(200), L1 2 -(110), L1 2 -(111) and L1 0 -(111) planes.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[5][6][7] Otherwise, the as-synthesized FePt NP always shows a fcc disorder structure, and annealing is required to form an L1 0 orderly phase, which has great prospects in the eld of magnetic storage, permanent magnets and magnetic catalysis. [8][9][10][11][12][13] The typical shape-anisotropy, element-distribution-anisotropy, and the meaningful disorder-order transition of concave-cube fcc-FePt NPs offer us an opportunity to study the evolution of microstructure and property for the anisotropic NPs during annealing.…”
Section: Introductionmentioning
confidence: 99%